Microsoft Word 2019 (Packt Publishing, 2019)
"The big secret about Microsoft Word is that using it the right way can save you hours of time and help you produce more impactful documents and reports. It's likely your currently using less than 20 percent of the functionality that Microsoft Word currently offers. Unlocking that 80% could have a huge impact on your productivity and career. In this in-depth Word 2019 course from Simon Sez IT, we not only teach you the most business-relevant features of Microsoft Word, you then get to put into practice what you learn through exercises at the end of each chapter."--Resource description page